Abangan-Islam or Making Islam Indigeneous? - Fachry Ali (Islamika Indonesiana, 2014)
Book Review:Mystic Synthesis in Java: A History of Islamization from the Fourteenth to the Early Nineteenth Centuries, by M.C. Ricklefs (Norwalk, CT: EastBridge, 2006), 275 pp. (English). Price $25.44. ISBN-13: 978-1891936616